Why Consider Aspirin for the Treatment of Vestibular Schwannoma? A Brief Review and Randomized, Double‐Blind, Placebo‐Controlled Study Proposal - D. Bradley Welling; Brian A. Neff; Fred F. Telischi; Neil Patel; Konstantina M. Stankovic (Laryngoscope Investigative Otolaryngology)
ABSTRACT Objective The primary objective of this study is to review the evidence for aspirin use to prevent the growth of vestibular schwannomas (VS) and to propose a prospective trial to determine the progression‐free survival of VS patients after up to 42 months of treatment with aspirin. Secondary study objectives are to determine the effect of aspirin on VS growth, hearing function, serum biomarker levels, and the quality of life, as well as to determine the tolerability of aspirin treatment and whether serum biomarker and salicylate levels predict the response to aspirin. Study Design Literature review. Setting Six academic and private medical centers. Methods Review of recent English literature regarding prophylactic aspirin use for VS. Results The retrospective reviews on the utility of aspirin to prevent VS growth are inconclusive. Eighty‐four patients have been enrolled in a prospective double‐blinded, placebo‐controlled trial thus far to determine the effect of aspirin on VS. Conclusions Completion of a robust study design is necessary. The current aspirin dose has been well tolerated, with minimal adverse events to date. Level of Evidence Review of retrospective studies: Level 4; Proposed randomized, placebo‐controlled, double‐blinded clinical trial: Level 2.